Prohibition Gangsters : The Rise and Fall of a Bad Generation - Mappen, Marc (Book collections on Project MUSE., 2013)
Based on FBI and other government files, trial transcripts, and scholarship, this book provides a lively narrative of shootouts, car chases, courtroom clashes, wire tapping, and rub-outs in the 1920s, the 1930s, and beyond. This book acknowledges how the gangsters and mobsters of the Prohibition generation - Al Capone, Lucky Luciano, and Dutch Schultz, among others - forever transformed organized crime from loosely associated gangs of the pre-Prohibition era into sophisticated, complex syndicates.